2002
DOI: 10.1536/jhj.43.495
|View full text |Cite
|
Sign up to set email alerts
|

Severe Mitral Regurgitation May Prevent Mural Thrombus Formation within the Left Ventricle with Systolic Dysfunction.

Abstract: SUMMARYThe protective effect of severe mitral regurgitation (MR) against left atrial thrombus formation has been well documented. It was also proposed that severe MR may prevent thrombus formation within the left ventricle (LV) with systolic dysfunction. Therefore, we investigated whether ischemic MR prevents thrombus formation within the LV in patients with systolic dysfunction. The study population was comprised of 1313 patients (1133 males, 180 females, age 56±18) with ischaemic LV dysfunction documented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[ 15 ] and Ozdemir et al . [ 16 ] inferred that severe MR may have a protective role in LVT formation, as it was identified only in the non-LVT group. However, other studies with AMI patients reported by Ascione et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] and Ozdemir et al . [ 16 ] inferred that severe MR may have a protective role in LVT formation, as it was identified only in the non-LVT group. However, other studies with AMI patients reported by Ascione et al .…”
Section: Discussionmentioning
confidence: 99%
“…The existent data support this hypothesis (Ozdemir et al, 2002). However, there are two circumstances in which the native ventricles (typically, the left) may form intracavitary thrombus.…”
Section: Ventricular Thrombosismentioning
confidence: 93%
“…low and slow flow with global or regional ventricular hypokinesis. Supporting this hypothesis, interestingly, it is that, in patients with mitral regurgitation in which the left ventricle is "auto" afterload-reduced by a parallel low afterload ejection pathway, the incidence of cavitary thrombus is decreased (Ozdemir et al, 2002). Second, and more importantly as an extreme case of regional ventricular dysfunction, ventricular aneurysm (most commonly in the left, and a result of prior myocardial infarction) characterized by regional ventricular wall dilatation and thinning with paradoxical expansion during ventricular systole (dyskinesis) is associated with a high rate of intracavitary thrombus formation (Natterson et al, 1995).…”
Section: Ventricular Thrombosismentioning
confidence: 96%
“…Ozdemir et al reported that patients with DCM accompanying severe MR had a lower incidence of LVT (6.8 vs. 34.2%). 8 LVT in that study was assessed by left ventriculography instead of TTE. Kalaria et al showed that the prevalence of DCM with MR was comparable between the LVT and LVT absent groups.…”
Section: Discussionmentioning
confidence: 99%